The Implementation of Aggression Replacement Training (ART) to Reduce Student Aggressive Behavior at SMA Kartika 1-2 Medan - Fauzi, Fikriyah Iftinan (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
The existence of services in guidance and counseling at school is to help overcome the problems experienced by students, one of the student problems that often occur is aggressive behavior. The purpose of this study was to determine the effectiveness of the application of Aggression Replacement Training (ART) in reducing student aggression behavior. This research uses the mixed method, of the research method uses Explanatory Sequential Design. This research was conducted at SMA Kartika 1-2 Medan in 2023. The research subjects were second-grade students totaling 25 students. The instruments used in the data collection process used three types, namely (1) Questionnaires; (2) observation; and (3) interviews. Data analysis includes (1) Descriptive analysis; (2) Normality test; (3) paired sample t-test; (3) homogeneity test; (4) Independent Sample t-test; and (5) N-Gain Score test. The results showed that students' aggression behavior tended to be high before the service, then after being given the Aggression Replacement Training (ART) technique service, students' aggression behavior according to. The decrease in student aggression behavior can be seen from the results of the Pre-test score, the average value is 76.3. After being given the service the Post-test score has an average value of 53.6. This shows that the application of Aggression Replacement Training (ART) can reduce students' aggressive behavior.